A SDN-SFC-based service-oriented load balancing for the IoT applications. (15th July 2018) - Chien, Wei-Che; Lai, Chin-Feng; Cho, Hsin-Hung; Chao, Han-Chieh
Abstract: Nowadays, with the rapid advance of network technology, the miniaturization of terminal equipment, and the trend of constant reduction of costs, the topic of IoT turns increasingly popular. As IoT becomes common in daily life, one can collect information at any time and in any environment, such as temperature, humidity, and PM2.5. Based on the analysis of such data, we can learn the degree of environmental comfort of a city, which is beneficial for the development of a smart city and other applications. However, the use of a large number of terminal equipment is likely to trigger huge demands of bandwidth, followed by the increase in the time of data transmission. In order to address this issue, this study proposed a service-oriented SDN-SFC load balance mechanism. It considered and classify the type and priority of service required by each terminal device. Then, it adopted the heuristic algorithm to plan the transmission paths among SFCs to reduce the load of each SF and improve the overall network performance. The simulation results indicate that the method proposed by this study can shorten the time of data transmission and achieve load balance.